Examining the Use of Discord Applications in Improving Science Learning Outcomes of Grade 7 Students - Nur Asrilah Maysi Zannah; Zakiyyah; Nurwanti Fatnah (International Journal of Education and Humanities, 2022)
During a pandemic like this, they were growing new regulations for conducting online learning, causing further problems in decreasing student learning outcomes in changing learning systems. This study aims to determine the factors that influence student learning interest in online learning with the Discord application, how the use of the Discord application is used in science learning and the effect of the Discord application on student learning outcomes in science learning. This research is a quantitative quasi-experimental study with a pretest-posttest control group design. The number of samples was 64 students from classes 7A and 7B, SMP Negeri 1 Depok, Depok District, Cirebon Regency. Data were obtained through pretest, posttest, questionnaire, interview, and documentation study. The results showed that the attractiveness of the Discord application as an online learning medium could influence students' interest in learning. The connectivity between teachers and students was more effective and efficient in online learning using the Discord application. The opportunity for students to play an active role during the learning process is incredible. The encouragement of motivation through the attitude of the teacher in learning. The influence of online learning media in the form of the Discord application on student learning outcomes in science subjects.